Tafsir Lingkungan: Kajian Ayat-Ayat Ekoteologi dan Konsep Ḥifẓ al-Bī`ah - Nur Kholisah; Saepul (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2025)
This article examines the interpretation of ecotheology by examining the verses of the Qur'an and the concept of Ḥifẓ al-Bīah (protecting the environment). This research is motivated by massive ecological crises, such as deforestation that reaches 1.8 million hectares per year and extreme water pollution due to domestic and industrial waste. This phenomenon shows the neglect of the human role as khalifah and demands a theological and practical response through the interpretation of environmental verses and the application of the concept of ḥifẓ al-bī'ah. The purpose of this research is to respond to the environmental crisis that continues to occur, such as deforestation and water pollution, which is the result of human actions that ignore their role as khalifah on earth. The method used is library research with a descriptive-qualitative approach. The research data consists of primary data in the form of the Qur'an, the book of tafsir and secondary data in the form of journal articles about the environment. The concept of Ḥifẓ al-Bīah is seen as an integral part of the main principles of sharia (maqāṣid al-sharī'ah) which aims to protect religion, soul, offspring, mind, and property. Based on the findings, this article recommends practical solutions such as reforestation and the adoption of a Zero Waste lifestyle to address environmental degradation. Thus, this article can enrich the Islamic scholarship surrounding the Qur'an and provide a moral, theological and practical framework for humans in general to be more active in environmental conservation and preservation efforts.